(untitled) - Chaplin, Hamako Ito. (New Haven, 1967)
The manual contains a number of sections, and each section is intended to aid the student in a particular way. Book 2, part I introduce about 25 charcters in each lesson and cover all characters in 35 lesson....
Keywords: Japanese language,Japanese language; Writing,Readers